Development in the early years socialization, motor development, and consciousness.[article]. - Kopp, Claire B
Patterns of socialization have changed in recent decades. Very young children now have fewer constraints on physical activities and greater freedom to assert themselves. This parenting style, I suggest has implications for developmental processes related to upright locomotion, the use of hands as tools, and an embodied consciousness. This review explores four issues. First, I summarize historical trends in patters of child-rearing and possible developmental consequences. Then I explore evolutionary patterns as a means to further development understanding of the initial phases of motor development. The third section reviews research on young humans' development paths toward locomotion and hand skills, examining early and current findings. Finally, I raise the issue of a body-action consciousness that emerges during infancy and the toddler years, suggests its developmental relevance, situate the theme in current developmental models, and explore applied implications -(from the author)
Keywords: Young children and technology; Conserved structures; Brain development